MIX OF BACTERIAL LYSATES IN A COMPLEX TREATMENT OF MUCOUS TUNIC OF ORAL CAVITY - V.M. Elizarova; S.Yu. Strakhova; E.E. Kolodinskaya (Union of pediatricians of Russia, 2007)
One of the most topical issues of pharmacotherapy in child age dentistry is the treatment of oral mucous tunic. The success of the treatment and prophylaxis of diseases is based on the availability of new high-active medications in market. The article analyzes the usage specificities of bacterial lysates mixes to cure acute dartrous stomatitis of childrenKey words: oral mucous tunic diseases, treatment, mix of bacterial lysates, children.